Laterality of previous stoke affects endovascular thrombectomy outcomes. (31st January 2022) - Bageac, Devin V; Gershon, Blake S; Chada, Deeksha; Siddiqui, Neha; Majidi, Shahram; Fifi, Johanna T; De Leacy, Reade
Abstract : Background: Investigations into the effect of previous stroke on thrombectomy outcomes have yielded conflicting results, and are limited by small sample sizes. We present the results of a large single center retrospective study aimed at investigating the effect of chronic stroke laterality on thrombectomy outcomes. Methods: A prospectively maintained database was queried for all thrombectomy cases conducted between December 2014 and January 2020, and patient imaging was prospectively reviewed for evidence of prior supratentorial infarction. Procedural, clinical, and demographic characteristics were recorded, and good clinical outcome was defined as a 90 day modified Rankin Scale (mRS) score of <2 or mRS score unchanged if baseline was >2. Results: The final analysis cohort included 555 patients, 79 of whom were found to have radiographic evidence of prior chronic infarcts. On univariate analysis, patients with any chronic supratentorial infarct achieved a lower rate of good clinical outcome than patients with no chronic infarct (22.8% vs 41.0%, p=0.0021). With regard to subgroups, this difference remained only in patients with ipsilateral (14.3%, p=0.0018) and bilateral (11.8%, p=0.015) lesions. Patients with chronic contralateral supratentorial infarcts were no less likely to achieve good outcomes (40.7%, p=0.98). After multivariate regression controlling for age, sex, and baseline mRS, chronic ipsilateral infarcts (OR 0.22, CI 0.07 to 0.67) and chronic bilateral infarcts (OR 0.19, CI 0.04 to 0.85) were the only independent predictors of poor outcome in endovascular thrombectomy patients. Conclusions: In this single center retrospective study of thrombectomy patients with chronic supratentorial infarcts, the laterality of the previous stroke significantly affected the likelihood of good clinical outcomes.